2005
DOI: 10.1038/sj.ejcn.1602203
|View full text |Cite
|
Sign up to set email alerts
|

Genomic effect of vitamin ‘C’ and statins within human mononuclear cells involved in atherogenic process

Abstract: Deregulated crosstalk within nuclear receptor/transcription factor family, comprising of peroxisome proliferator-activated receptors (PPARs) and liver X receptor-a (LXR-a), can give rise to cooperativity between lipid peroxidation and inflammation leading to atherogenic process. The present study addressed to explore the effect of statins and vitamin 'C' on transcriptional expression of genes coding for this nuclear receptor/transcription factor family within mononuclear cells revealed for the first time that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…22-R hydroxycholestrol was more potent in activating LXR-a compared to Ascorbic acid ? 22-ROH cholesterol [11]. An increase of 55 % in LXR-a gene expression at RNA level was observed in Atorvastatin ?…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…22-R hydroxycholestrol was more potent in activating LXR-a compared to Ascorbic acid ? 22-ROH cholesterol [11]. An increase of 55 % in LXR-a gene expression at RNA level was observed in Atorvastatin ?…”
Section: Resultsmentioning
confidence: 90%
“…The present study tries to enlighten the dermatologists about the recently discovered immunomodulatory effects of statins in order to encourage research on the use of these safe and inexpensive agents in the treatment of various immunological dermatologic conditions [21,22]. Keeping this in mind and data accumulated on the activation of LXR-a by Statins [2,23] and Vitamin C [11], made it important for us to do a preliminary test on the effect of these compounds in the psoriatic lesional keratinocytes. Interestingly, the cultured psoriatic keratinocytes treated with both Ascorbic acid and Atorvastatin along with 22-R hydroxycholestrol reverted the characteristics to the normal counterpart, thereby proving the role LXR-a may play in the pathophysiology of psoriasis (Fig.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…LXR-α has been widely recognized as a master gene that plays a crucial role in cholesterol homeostasis, lipid peroxidation and inflammation responsible for the initiation of CHD and its clinical implications [1][2][3][4][5][6][7] . Apart from the observed protective effects of LXR-α agonists in the various cellular and animal model systems [8][9][10][11][12][13][14] , the importance of LXR-α in pathogenesis of CHD is further highlighted by the studies from our laboratory which showed that both statins (drug of choice for CHD) and vitamin C have an inherent capacity to upregulate LXR-α expression [15] and also that human CHD subjects (with or without hyperlipidemia) have conspicuously higher blood cellular LXR-α mRNA expression as compared to their normal healthy counterparts [16] . However, synthetic agonists for the LXR-α activation designed as therapeutic agents for the regression of coronary atherosclerosis did not meet the expected success.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro and in vivo studies in animal models of atherosclerosis have shown that LXR-α agonists can attenuate lesion progression and also lead to regression of an already established plaque [8][9][10][11][12][13][14] . The observation that statins as well as vitamin C, both have an inherent ability to upregulate LXR-α [15] further underline its importance. Findings from our laboratory have demonstrated that both normolipidemic and hyperlipidemic human coronary heart disease (CHD) subjects have significantly higher expression of blood cellular LXR-α as compared to the corresponding controls [16] .…”
Section: Introductionmentioning
confidence: 99%